ENGLISH LEARNING BASED STUDENTS' ECONOMIC PURPOSES - Islam, Raudhatul; Hamdani, Beny; Zainuddin; Ferdiyanto, Feri; Safila, Risa (Teaching English as Foreign Language, Literature and Linguisticss, 2022)
Abstract This research was conducted to describe the real condition and situation of English subject concerned to students' Economic purposes. The aim of this research is to describe the English teaching and learning process, to know the kind of teaching method and the teaching material applied, to describe the teaching media used in technology era by the lecturer and to know the lecturer's way to assess the students' English improvement. Descriptive qualitative design is used in this study. The researcher used observation scheme, questionnaire and formal interview to complete the data as the instrument. The results of the questionnaire showed from 28 students there were 21 students enjoyed the class but the others are less interesting in this course. From the data, it answered how the impact in teaching and learning process was. The lecturer liked to use cooperative learning for teaching method and the lecturer used management book English version for the main source. Based on the result of interview and observation scheme data, the lecturer almost used technology moreover in this 4.0 era. Moreover, the researcher found the way lecturer assess the students' English skill. The conclusion was English learning concerned to ESP run well due to it proved with the students enjoyed the English teaching and learning.